Consolidated legal texts for the Special Court for Sierra Leone - Jalloh, Charles (Martinus Nijhoff Publishers, 2007)
The creation of the first treaty-based international criminal court with a mixed jurisdiction ratione materiae by the UN and Sierra Leone is said to be an important step for international criminal justice because it is a leaner ad hoc court.